2022
DOI: 10.1177/20552076221145856
|View full text |Cite
|
Sign up to set email alerts
|

Development of a health information system to promote emergency care pathways: A participatory design study

Abstract: Objective The successful development and implementation of sustainable healthcare technologies require an understanding of the clinical setting and its potential challenges from a user perspective. Previous studies have uncovered a gap between what emergency departments deliver and the needs and preferences of patients and family members. This study investigated whether a user-driven approach and participatory design could provide a technical solution to bridge the identified gap. Methods We conducted four wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Echoing these findings, Verma et al [ 39 ] investigated the level of eHealth literacy among older adults and caregivers and found that one main barrier to the adoption of eHealth was a lack of familiarity with the tools available. In the development phase of CCL for patients [ 16 ], decisions had to be made for the system to work in a clinical setting. One decision was the use of an interface design, which did not allow us to integrate well-known functions, for example, from email or application symbols.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Echoing these findings, Verma et al [ 39 ] investigated the level of eHealth literacy among older adults and caregivers and found that one main barrier to the adoption of eHealth was a lack of familiarity with the tools available. In the development phase of CCL for patients [ 16 ], decisions had to be made for the system to work in a clinical setting. One decision was the use of an interface design, which did not allow us to integrate well-known functions, for example, from email or application symbols.…”
Section: Discussionmentioning
confidence: 99%
“…An update of the Medical Research Council’s guidelines for developing and evaluating complex interventions in health care states that appropriate users should be involved in every part of the development, process, and outcome analysis of a complex intervention to ensure sustainable interventions [ 50 ]. In line with best practices, the information system has been developed together with representatives of future users of the system, including health care professionals, managers, patients, family members, and IT specialists [ 16 ]. For decades, the ED context has been a hectic environment [ 4 , 42 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations